A new species of Cirolana Leach, 1818 (Isopoda, Cymothoidea, Cirolanidae), from Havelock Island, Andaman Sea, northern Indian Ocean - Anil, Pathan; Bruce, Niel L.; Jayaraj, Kadeparambil Arjunan (Zootaxa, 2024)
Cirolana swaraj sp. nov. was collected from brackish-water Neil Lagoon on Havelock Island, South Andaman and is described and illustrated in detail. Cirolana swaraj sp. nov. can be distinguished by: frontal lamina 2.2 times as long as greatest width, lateral margins slightly widening to rounded anterior margin; pereonite 1 dorsal anterior mid-region with convex boss covered with fine ridges, pereonites 1–7 each with a single transverse impressed line, posterior margin with 18, 18, 17 and 12 tubercles on pereonites 4−7 dorsal posterior margins respectively; pleonites 4−5 each with prominent median tubercle, 4 and 2 tubercules on each side of pleonites 4−5; pleotelson dorsal surface with sub-median double row of 5 tubercules, posterior lateral margins straight, posterior margin narrowly rounded with 6 robust setae and plumose marginal setae extending anteriorly to mid-length; uropodal exopod lateral margin with eight robust setae and a continuous row of plumose marginal setae. A key to the marine and estuarine genera of Cirolanidae of the northern Indian Ocean is given.